(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In the present times, when use of Internet and it’s services has become so widespread, Personal privacy has become of the utmost priority of every person. One of the ways to safeguard their personal Information is the use of cryptography. This paper discusses the modern cryptographic Algorithms that have been in action in the past few decades. Different symmetric and asymmetric algorithms ensure that data is completely secure, and if a third party intercepted the message, it becomes difficult for the person to decipher the particular data due to multilevel encryption levels. Keywords: Modern Cryptographic Algorithms, AES, DES, 3DES, RSA, Diffie-Hellman, DSA, SEAL,RC4.